2002
DOI: 10.1002/marc.200290007
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Polymer Swelling Employing a Linear Variable Differential Transformer: CO2 Effects on SBS Triblock Copolymer

Abstract: A linear variable differential transformer (LVDT) was employed to evaluate CO2‐polymer plasticization. Preliminary results on polystyrene‐block‐polybutadiene‐block‐polystyrene (SBS) elastomer are presented. At 22 °C under CO2 pressure, SBS undergoes compression due to hydrostatic pressure. However, sample expansion occurs upon depressurization. At 45 °C, SBS undergoes swelling of 0.7% due to CO2 plasticization, while no post‐pressurization expansion is observed. The contrasting result is explained by change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Indeed, for every polymer, the CO 2 mass uptake is increased by about 40 to 72% when the CO 2 pressure is raised from 5 MPa to 10 MPa whereas only a modest increase of about 4 to 20% CO 2 mass uptake is observed between 10 MPa and 15 MPa. This nonlinear relation between the solubility and the pressure increase has been reported for other rubbery polymers [22,27,[30][31][32]. Tomasko et al [33] explained that at high pressure, CO 2 sorption is no longer proportional to CO 2 pressure.…”
Section: 2b Co 2 Sorptionsupporting
confidence: 53%
See 1 more Smart Citation
“…Indeed, for every polymer, the CO 2 mass uptake is increased by about 40 to 72% when the CO 2 pressure is raised from 5 MPa to 10 MPa whereas only a modest increase of about 4 to 20% CO 2 mass uptake is observed between 10 MPa and 15 MPa. This nonlinear relation between the solubility and the pressure increase has been reported for other rubbery polymers [22,27,[30][31][32]. Tomasko et al [33] explained that at high pressure, CO 2 sorption is no longer proportional to CO 2 pressure.…”
Section: 2b Co 2 Sorptionsupporting
confidence: 53%
“…But depending on the polymer, the knowledge of CO2/polymer interactions is more or less accessible or sometimes poorly affordable. Glassy amorphous polymers are the most studied polymers [12,13], semi crystalline polymers are commonly studied [13][14][15][16] whereas reinforced, filled, or biphasic materials are becoming more and more studied [14,17,18] However studies (e.g refs [16,[19][20][21][22]) are rather scarce when dealing with the behavior of elastomers (neat or filled) in CO 2 . The reasons are twofold: i) rubbery polymers are expected to be highly deformable in CO 2 (involving a high swelling), ii) the sorption/desorption stages are fast.…”
Section: -Introductionmentioning
confidence: 99%
“…Using solubility data for related polymers, Tuminello predicted that PTFE should be soluble in supercritical CO 2 (scCO 2 ) at very high temperatures and pressures [6]. In earlier studies, we found that scCO 2 plasticized perfluorinated polymers and acted as a processing aid [7][8][9]. Building on that work, we report here on post-processing properties, particularly creep, of PTFE treated with scCO 2 and compare these properties with those of PTFE annealed at ambient pressure.…”
Section: Introductionmentioning
confidence: 86%
“…First of all, the swelling of polymers is a well-known consequence of fluid sorption [4,5] and this effect is severe with elastomer components [6][7][8][9][10]. The volume change phenomenon has been widely discussed in the literature, particularly in the case of carbon dioxide (CO 2 ) [1,6,9,[11][12][13][14] and to a lesser extent hydrogen (H 2 ) [15]. Reported data concern variety of thermoplastics (PEEK, PS, LLDPE, PTFE, PMMA, PET, PP, PVDF, … [12]) in CO 2 , but also rubbers and elastomers such as HNBR [1,13,16], NBR [14,16], EPDM [14,16], SBS block [12], PDMS [17,18], FKM [16], PTFE [16], ACM [16], VMQ [16], and rubber polymer [19].…”
Section: Introductionmentioning
confidence: 99%
“…The volume change phenomenon has been widely discussed in the literature, particularly in the case of carbon dioxide (CO 2 ) [1,6,9,[11][12][13][14] and to a lesser extent hydrogen (H 2 ) [15]. Reported data concern variety of thermoplastics (PEEK, PS, LLDPE, PTFE, PMMA, PET, PP, PVDF, … [12]) in CO 2 , but also rubbers and elastomers such as HNBR [1,13,16], NBR [14,16], EPDM [14,16], SBS block [12], PDMS [17,18], FKM [16], PTFE [16], ACM [16], VMQ [16], and rubber polymer [19]. As an illustration, Bonavoglia et al [11] with the same apparatus described by Rajendran et al measured by direct visualization the swelling [15].…”
Section: Introductionmentioning
confidence: 99%